An introduction to microwave measurements - Basu, Ananjan (CRC Press, 2015)
This book starts with a brief overview, and then gives a short summary of the basic theory and the building blocks required to understand and use microwave measurement techniques. After a brief description of older measurement techniques (slotted wave guide etc.) the book gives a fairly detailed description of the vector network analyzer and the spectrum analyzer, which form the backbone of modern microwave measurements. Advanced topics such as pulsed measurements and non-linear network analysis are only mentioned in passing